Upaya Promotif Kesehatan Gigi dan Mulut di Madura, Jawa Timur - Ninuk Hariyani; Dini Setyowati; Anisa Nur Halimah; Arie Wahyu Prananta; Sri Hidayati; Mohtazul Farid; Hirmadhani Rahma Anindita (Jurnal Pengabdian Sumber Daya Manusia, 2022)
Dental and oral health problems are closely related to people's productivity. Data in Madura shows that many areas in Madura have many dental and oral problems, in which the majority of them have not received any treatment. Good quality dental and oral health education program is still needed in Madura. This community service activity is carried out through a dental and oral health promotion program that is developed according to the resources, facilities and infrastructure owned by the target partners. The activity chosen as a solution at this stage is dental health counseling, given to the target group of women and community leaders who can later be empowered by becoming dental cadres or agents of change. In addition, counseling among children was also carried out using the story telling method. The results for these two target groups indicate an increase in their knowledge which is expected to lead to improved behavior related to dental health in Madura in the future.